Ghana's COCBOD incorporates CGIAR science into training materials for climate resilient cocoa production (targeting a potential 800,000 farmers) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The Ghanaian cocoa sector made important strides towards climate-resilience under COCOBOD leadership. Exposure maps were combined with exposure gradient specific CSA practices in a national training manual of obligatory use for all public and private extension targeting the 800,000 cocoa farmers in the country. Additional CSA specific training materials were developed with World Cocoa Foundation which enabled the establishment of 4 pilots are on-going with private sector actors to study how to incentivize CSA uptake by farmers.